2004
DOI: 10.1002/gene.20019
|View full text |Cite
|
Sign up to set email alerts
|

Transition nuclear proteins are required for normal chromatin condensation and functional sperm development

Abstract: The histone-to-protamine transition is important in the formation of spermatozoa. In mammals this involves two steps: replacement of histones by transition nuclear proteins (TPs) and replacement of TPs by protamines. To determine the functions of the TPs and their importance for sperm development, we generated mice lacking both TPs, since mice lacking only TP1 or TP2 were fertile. Our results indicated that TP1 and TP2 had partially complemented each other. In mice lacking both TPs, nuclear shaping, transcript… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
130
0
6

Year Published

2004
2004
2017
2017

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 171 publications
(139 citation statements)
references
References 56 publications
3
130
0
6
Order By: Relevance
“…have reported that during the normal process of spermiogenesis strand breaks are introduced in step 9 -11 spermatids and that these are associated with the condensation of the germ cell DNA and replacement of histones by protamines, but that after stage 11 all DNA breaks within the normal spermatid have been repaired and the histones have been completely replaced by protamines. Zhao et al (2004) have shown that transition proteins (TP) involved in the histone to protamine transition are also required for normal chromatin condensation, for reducing the number of DNA breaks and preventing a loss of genetic integrity. In the mouse transition proteins are expressed in step 10 to step 14 spermatids and the onset of protamine expression has been detected in step 10 spermatids using immunohistochemistry.…”
Section: Discussionmentioning
confidence: 99%
“…have reported that during the normal process of spermiogenesis strand breaks are introduced in step 9 -11 spermatids and that these are associated with the condensation of the germ cell DNA and replacement of histones by protamines, but that after stage 11 all DNA breaks within the normal spermatid have been repaired and the histones have been completely replaced by protamines. Zhao et al (2004) have shown that transition proteins (TP) involved in the histone to protamine transition are also required for normal chromatin condensation, for reducing the number of DNA breaks and preventing a loss of genetic integrity. In the mouse transition proteins are expressed in step 10 to step 14 spermatids and the onset of protamine expression has been detected in step 10 spermatids using immunohistochemistry.…”
Section: Discussionmentioning
confidence: 99%
“…The role of TPs and their structural properties are not well understood, but they play an important role in the condensation of the spermatid nucleus, as mice with deletions of both major transition proteins, TP1 and TP2, are infertile Zhao et al 2004]. As demonstrated by Shirley and colleagues , the interplay between TPs and protamines is quite complex.…”
Section: Transition Proteinsmentioning
confidence: 99%
“…Some mutant, transgenic, and gene-targeted males are infertile because of defective spermiogenesis. The infertility of such males has been overcome by injection of spermatids into normal oocytes (6)(7)(8)(9). However, if the gonads of animals of interest lack germ cells, cloning would be the only way to propagate such lines.…”
mentioning
confidence: 99%